Distribution and histological structure of peyer's patches in the large intestine of three-month-old calves - Saw, Po Po; Abu Bakar @ Zakaria, Md Zuki; Saad, Mohd Zamri; Omar, Abdul Rahman; Abd Wahid, Mohd Effendy (Veterinary Association Malaysia, 2005)
Distribution and histological structure of aggregated lymphoid tissues (Peyer's patches) of the large intestine were evaluated in three-month-old calves. The first patch was situated in the ileocaecal entrance, second patch in the proximal colon and third in the rectum. The length ofPeyer's patches in the proximal colon varied from 4 to 8 cm. Macroscopically, the patches at ileocaecal entrance and proximal colon were clearly seen, whereas the rectal patch was inconspicuous. Histologically, the Peyer's patches of the large intestine consisted of lymphoglandular complex and lamina propria nodules. The lymphoglandular complex was located within the submucosa that contains epithelial diverticula, which extends from muscularis mucosae. The lamina propria nodules were located in the lamina propria. The propria nodules were surrounded by wide crypts, lined by distinct follicle-associated epithelium and lacked goblet cells. The lymphoglandular complexes were covered with distinct follicle-associated epithelium with numerous intraepithelial lymphocytes and lacked goblet cells. Intraepithelial lymphocytes were distributed in the epithelial layer of the large intestine and formed a unique lymphocyte population. Some Peyer's patches ofthe large intestine were similar to that of jejunal Peyer's patches as they contained broad follicles, distinct corona areas and wide interfollicular areas.